INTRA-ARTICULAR INJECTION OF SODIUM HYALURONATE IN THE TREATMENT OF KNEE OSTEOARTHRITIS - Bülent Bütün; Cahit Kaçar; Deniz Evcik (Archives of Rheumatology, 2002)
Objective: To determine the effects of intra-articular hyaluronan on the symptoms of knee osteoarthritis (OA). Methods: Twenty-eight patiets with bilateral knee OA (ACR criteria) were included in this double-blind, randomised and placebo-controlled trial. All of them (total 56 knees) had grade II or III degeneration radiologically according to Kellgren-Lawrence method. One knee for every patient was assigned randomly by active treatment and applied 2 ml solution of sodium hyaluronate intra-articularly (15 mg/ml) and the contralateral knee was accepted as placebo and injected 2 ml physiological saline, within the same procedure, once a week for 3 consecutive weeks. Efficacy on pain, function, stiffness, motion, activity and tolerability were evaluated with detailed parameters at weeks 1, 2, 3 and 5. Results: No side effects developed during a 5 week period. Both groups, according to patients, were improved at 5 week compared with baseline but there was no statistically significant difference between two groups. The efficacies of hyaluronan and saline solutions were similar on the all parameters. Conclusion: It is concluded that sodium hyaluronate offers no significant benefit over plcebo during a 5 week treatment period.